The role of justice in honest behaviors: epistemic privileges, plurality of justice and dishonesty as a way to recover from injustice (2023)
We conducted a research program divided into three parts, corresponding to the three chapters that comprise the document. In the first part, we conceptually explore what honesty is and propose a model of honesty based on the concept of epistemic privilege. This will involve critiquing a significant portion of studies on honesty that are based on the idea of surveillance and norm compliance. The conclusion of this chapter will be essentially negative, indicating that a comprehensive explanation of honesty seems to require going beyond norms and surveillance. The central contribution of this chapter will be proposing our conceptual model of honesty and providing tools to critique existing models. Given that there is a literature connecting, albeit without entirely satisfactory development, experiences of injustice with being dishonest, the concept of justice appears to be a promising candidate for exploring explanations of honesty beyond surveillance and norms. In Chapter 2, we develop a model of justice that allows us to form a hypothesis about how justice operates psychologically in the form of a belief in whether the world is just or not. In addition to this model, in the chapter, we propose and validate a psychometric scale to measure what we call the pluralistic scale of belief in a just world. The central contribution of this chapter will be proposing a conceptual model of justice and a new psychometrical scale to measure the belief in a just world derived from this model. This leads us to the third chapter, in which we use the justice model developed in Chapter 2 to design and implement an experimental program to manipulate conditions of justice and injustice that enable us to evaluate the effects of experiences of justice and injustice on honest and dishonest behaviors. In this chapter, we propose the central hypothesis of the thesis, which is the performance correction hypothesis, and provide some partial evidence to support it. The central contribution of this chapter is to propose a novel explanation of honesty based in the idea of performance correction and partial empirical evidence to support it.